The influence of body mass index on sensorimotor block and vasopressor requirement during spinal anaesthesia for elective caesarean section - Ngaka, Tshebeletso Christian (Department of Anaesthesia, 2017)
Background: It has been suggested that the dose requirement for spinal anesthesia (SA) is lower in obese patients for cesarean delivery. In this prospective, observational, non-inferiority study we tested the hypothesis that obesity would not have a clinically important effect on vasopressor requirements or block height. Methods: Two groups of 25 parturients, Group O (BMI >40 kg/m²) and Group N (BMI <32 kg/m²) requiring elective cesarean delivery were recruited. All patients received 10 mg intrathecal hyperbaric bupivacaine co-administered with 10 μg fentanyl. Dermatomal levels were assessed at 5 and 25 minutes after SA, and at completion of surgery, using light touch and cold sensation in response to ethyl chloride. The primary outcomes were phenylephrine requirement in the first thirty minutes following spinal anesthesia, and maximum block height, measured by the sensation of touch and cold. Secondary outcomes were total phenylephrine dose required, changes in hand grip strength, and peak flow rate. Results: There were no significant between-group differences in median block height as assessed by touch at 5 or 25 minutes, or by temperature at 5 minutes. At 25 minutes, there was a two-dermatome difference in median block height for loss of temperature sensation between Group O and Group N (T2 vs. T4, 95% confidence interval (CI) of the difference in medians 0-2 dermatomes). No blocks extended to cervical dermatomes. The median (range) phenylephrine dose for the first 30 minutes was 150 μg (0-900 μg), and 100 μg (0-1250 μg) in Group N and O respectively. The 95% CI for the difference between the two median doses was -150 μg to 100 μg. There were no differences in median percentage reductions in peak flow rate or median hand grip strength after SA. Mean surgical time was longer in Group O than in Group N (49.1 vs 39.4 minutes, 95% CI difference 1.7 to 17.7 minutes). The mean time for recovery of touch sensation to T10 was longer in Group O (152 vs 132 minutes, 95% CI difference 3.8 to 36.2 minutes). No analgesic supplementation was required. Conclusion: Only a minor increase block height as assessed by temperature occurred in Group O at 25 minutes. Vasopressor requirements during the first 30 min of SA were equivalent. Time for regression of SA block level was longer in the Group O, which may be beneficial considering the longer surgical time. A dose of spinal bupivacaine 10 mg for single-shot SA should not be reduced in morbidly obese parturients.